Kemampuan Guru Dalam Mengenalkan Etnomatematika Pada Anak Usia Dini ( Studi Kasus Di Tk Kartika Xix-3 Cimahi) - Komala, Komala; Sentana, Fifiet Tresna (Universitas Hamzanwadi, 2020)
This study aims to look at the ability of teachers to introduce ethnomatematics in early childhood in TK Kartika XIX-3 Cimahi City. This research is included in qualitative research. Early childhood research in TK Kartika XIX-3 Kota The research method used in this study is a qualitative method, by providing descriptive analysis of the focus of research that has been formulated, based on the facts of teacher learning actions in TK Kartika XIX-3 Cimahi. This research emphasizes the meaning of the act of teacher learning in introducing ethno-mathematics to early childhood. The purpose of this study was to determine how the teacher's ability to introduce ethnomatematics at TK Kartika XIX-3 in Cimahi City. While the benefits of research are to help develop the theory, knowledge and practice of the ability of teachers to build ethnomatematics literacy. This study produced several findings related to the application of the teacher's ability to introduce ethnomatics in early childhood. Based on the results of the study it was found that in general ethnomatics before learning are no different from learning that is normally given on a daily basis. Furthermore, after the action is carried out, an overview of ethnomatic literacy is obtained showing that there are findings related to ethnomatatics given to learning at TK Kartika XIX-3 in Cimahi City, including teachers having been able to present learning with ethnomatic literacy content, thus giving an impact on ethnomatic ability child. The results showed that the teacher was able to introduce and improve the ethnomatic literacy of children in the classes he was in.